Analysis of Active Site Architecture and Reaction Product Linkage Chemistry Reveals a Conserved Cleavage Substrate for an Endo-alpha-mannanase within Diverse Yeast Mannans. Issue 4 (14th February 2020) - Jones, Darryl R.; Xing, Xiaohui; Tingley, Jeffrey P.; Klassen, Leeann; King, Marissa L.; Alexander, Trevor W.; Abbott, D. Wade
Abstract: Yeast α-mannan (YM) is a densely branched N-linked glycan that decorates the surface of yeast cell walls. Owing to the high degree of branching, cleavage of the backbone of YM appears to rely on the coupled action of side-chain-cleaving enzymes. Upon examining the genome sequences of bovine-adapted Bacteroides thetaiotaomicron strains, isolated for their ability to degrade YM, we have identified a tandem pair of genes inserted into an orphan pathway predicted to be involved in YM metabolism. Here, we investigated the activity of one of these enzymes, a predicted endo-mannanase from glycoside hydrolase (GH) family 76 (BtGH76-MD40). Purified recombinant BtGH76-MD40 displayed activity on structurally distinct YMs from Saccharomyces cerevisiae and Schizosaccharomyces pombe . Linkage analysis of released oligosaccharide products from S. cerevisiae and S. pombe mannan determined BtGH76-MD40 targets a specific linkage that is conserved in structurally diverse YM substrates. In addition, using two differential derivatization methods, we have shown that there is an absolute requirement for undecorated d -mannopyranose in the −1 subsite. Determination of the BtGH76-MD40 X-ray crystal structure and structural superimposition and molecular docking of a branched alpha-mannopentatose substrate supported these findings. In contrast, BtGH76-MD40 can accommodate extended side chains in the +1 and −2 subsites, highlighting that a single alpha-1, 6-mannosyl residue is a prerequisite for activity, and cleavage occurs at the reducing end of the undecorated monosaccharide. Collectively these results demonstrate how acquisition of new enzymes within extant pathways contributes to the functional abilities of saccharolytic bacteria persisting in complex digestive ecosystems. Graphical abstract: Image 1 Highlights: Yeast mannan (YM) is a highly branched polysaccharide with species-dependent structural diversity. An enzyme has been found within the bovine rumen that cleaves the backbone of YM. Cleavage requires the presence of an unbranched 6-linked mannose. Glycosidic linkage analysis and crystallography elucidate the nature of interactions.